The bursa dependence of chicken thymus-derived lymphocyte surface immunoglobulin. - Hudson, L (1975)
Thirty-three plus or minus 5 per cent of chicken blood lymphocytes were positively labelled by radioiodinated rabbit anti-chicken light chain antibody within 7 days of exposure of autoradiographs. After thymectomy, 93 plus or minus 1 per cent of lymphocytes were positive: conversely, following bursectomy only 5 plus or minus 3 per cent of cells showed positive labelling and then at a very low level. Hence, under these conditions of short-term exposure autoradiography, only B cells carried readily demonstrable immunoglobulin. If the sensitivity of the technique was increased by long-term exposure of the autoradiographs, immunoglobulin was demonstrable on all blood lymphocytes, including the T cells. In addition, 39 plus or minus 6 per cent of thymocytes were shown to carry immunoglobulin by the more sensitive technique. In both cases, however, this T-lymphocyte surface immunoglobulin was reduced, and in some cases absent, after bursectomy. At no stage, with either technique, did the grain count on the erythrocytes reach the control level of lymphocytes treated with 125I-labelled anti-keyhole limpet haemocyanin antibody. It seems likely that T-cell immunoglobulin is not an endogenously synthesized product but is acquired indirectly from the B lymphocytes.